Novel genetic polymorphisms associated with severe malaria and under selective pressure in North-eastern Tanzania. - Ravenhall, M; Campino, S; Sepúlveda, N; Manjurano, A; Nadjm, B; Mtove, G; Wangai, H; Maxwell, C; Olomi, R; Reyburn, H; Drakeley, CJ; Riley, EM; et al. (Public Library of Science, 2018)
Significant selection pressure has been exerted on the genomes of human populations exposed to Plasmodium falciparum infection, resulting in the acquisition of mechanisms of resistance against severe malarial disease. Many host genetic factors, including sickle cell trait, have been associated with reduced risk of developing severe malaria, but do not account for all of the observed phenotypic variation. Identification of novel inherited risk factors relies upon high-resolution genome-wide association studies (GWAS). We present findings of a GWAS of severe malaria performed in a Tanzanian population (n = 914, 15.2 million SNPs). Beyond the expected association with the sickle cell HbS variant, we identify protective associations within two interleukin receptors (IL-23R and IL-12RBR2) and the kelch-like protein KLHL3 (all P<10−6), as well as near significant effects for Major Histocompatibility Complex (MHC) haplotypes. Complementary analyses, based on detecting extended haplotype homozygosity, identified SYNJ2BP, GCLC and MHC as potential loci under recent positive selection. Through whole genome sequencing of an independent Tanzanian cohort (parent-child trios n = 247), we confirm the allele frequencies of common polymorphisms underlying associations and selection, as well as the presence of multiple structural variants that could be in linkage with these SNPs. Imputation of structural variants in a region encompassing the glycophorin genes on chromosome 4, led to the characterisation of more than 50 rare variants, and individually no strong evidence of associations with severe malaria in our primary dataset (P>0.3). Our approach demonstrates the potential of a joint genotyping-sequencing strategy to identify as-yet unknown susceptibility loci in an African population with well-characterised malaria phenotypes. The regions encompassing these loci are potential targets for the design of much needed interventions for preventing or treating malarial disease.